TYPES OF VIOLENCE AGAINST WOMEN IN THE FAMILY (World Bulletin of Social Sciences, 2024)
This article shows that domestic violence against women is often hidden behind closed doors. Through an extensive literature review, the study aims to identify and analyze various forms of violence, including psychological, physical, sexual, and economic violence. The methods used included a comprehensive review of the academic literature and relevant research. An analysis of studies is presented, and a nuanced understanding of the multifaceted nature of domestic violence against women is provided. The article concludes with key findings and suggests strategies for addressing and mitigating the effects of violence against women in the family context.
Keywords: Violence against women; domestic violence; intimate partner violence